INOVASI DESAIN KEMASAN PRODUK RUMAH MAKAN BONELO - Muhammad, Ashar; Kalsum, Ummi (Politeknik STIA LAN Makassar, 2023)
The culinary industry is currently growing rapidly in Indonesia, one of which is a restaurant that is easy to find with a variety of food and beverage dishes. The development of the restaurant business has caused a high level of competition to demand restaurants to innovate in order to survive in the business world. Packaging design is a strategy that companies can use to compete in the business world. Bonelo Restaurant (RM) is one of the restaurants in Makassar City. RM Bonelo has problems with product packaging where the food packaging is less attractive and easily damaged so that the research produces the output of a product packaging design innovation. In this study, it used qualitative methods with the method of collecting interviews and observations. With the innovation of product packaging on RM Bonelo packaging, it can increase sales and profits.